2021
DOI: 10.1021/acsnano.1c00390
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Giant Enhanced Raman Scattering by Sulfur Chains Encapsulated inside Single-Wall Carbon Nanotubes

Abstract: In this work, we explain the origin and the mechanism responsible for the strong enhancement of the Raman signal of sulfur chains encapsulated by single-wall carbon nanotubes by running resonance Raman measurements in a wide range of excitation energies for two nanotube samples with different diameter distributions. The Raman signal associated with the vibrational modes of the sulfur chain is observed when it is confined by small-diameter metallic nanotubes. Moreover, a strong enhancement of the Raman signal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Finally, the Silicon Raman intensity is also dependent on the laser excitation energy [37], which should be taken into account to have a correct data normalization [38,39]. The RRPs are then corrected also for the dependence of the Raman intensity of Silicon (more information on this calibration procedure is reported in the SI).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the Silicon Raman intensity is also dependent on the laser excitation energy [37], which should be taken into account to have a correct data normalization [38,39]. The RRPs are then corrected also for the dependence of the Raman intensity of Silicon (more information on this calibration procedure is reported in the SI).…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur content of S@SWCNT-121 and S@SWCNT-777 is similar to values of S@SWCNT samples produced in a similar procedure by Nascimento et al using thermal post-treatment to remove external sulfur following an initial 48 h exposure to sulfur vapour. 49 Sulfur contents obtained from TGA differ from those determined via XPS, which reveals sulfur contents of S@SWCNT-121, S@SWCNT-777 and S@TE7 containing 14.7 wt%, 9.3 wt% and 14.4 wt%, respectively, to a maximal probable depth of approximately 10 nm (see ESI, † Table S1). Differences in the quantity of sulfur determined may be due to variation between batches (XPS was conducted on samples produced following testing) or may stem from heterogeneity of sulfur concentration throughout the sample volume.…”
Section: Energy Advances Papermentioning
confidence: 96%
“…Previous reports have explored the origins of these doublet peaks located around 320 cm À1 and 400 cm À1 , in detail. 49,51 Nascimento et al predict that a strong doublet peak would be observed in a SWCNT of the chirality (7,6) and suggest these peaks arise from splitting from degenerate stretching modes of a polymeric sulfur chain due to quantum confinement effects enforced by the surrounding CNT. 49 Geometry optimisation of similar diameter SWCNTs suggests a helical conformation of the sulfur parallel to the tube wall is the most energetically favourable conformation.…”
Section: Energy Advances Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the relationship between the morphology and SERS property of silver nanostructures is relatively scarce [ 23 ]. Therefore, by adjusting different parameters, the preparation of silver nanostructures with different morphologies and the rapid screening of optimal Raman enhancement performance can be realized [ [24] , [25] , [26] ], which is of great significance for constructing an accurate COVID-19 detection platform [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ].…”
Section: Introductionmentioning
confidence: 99%